Pengaruh Lingkungan Sosial, Potensi Diri dan Peluang Karir Terhadap Minat Untuk Melanjutkan Pendidikan Tinggi (Studi Pada Sekolah SMAN 1 Waru Pamekasan) - Rica Ayu Permata Sari; Muhammad Ridwan Basalamah; Ita Athia (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of the social environment, self-potential, and career opportunities on students' interest in continuing higher education at SMAN 1 Waru Pamekasan. This type of research is quantitative using an associative approach. The study population included all 364 students in grades X, XI, and XII, with a sample of 191 respondents determined using the Slovin formula. The sampling technique used was non-probability sampling with a convenience sampling method. Data collection used a questionnaire method that will be given through (online) media using Google Form with a five-point Likert scale. The data obtained were analyzed using the SPSS program version 28. The results of the study indicate that the social environment, self-potential, and career opportunities simultaneously have a positive and significant effect on students' interest in continuing higher education. Partially, each variable also shows a positive and significant effect on interest in continuing higher education. However, this influence is not fully optimal because it is still influenced by economic limitations, family cultural pressures, and minimal career guidance. Therefore, it is necessary to strengthen the role of schools and environmental support in encouraging the sustainability of higher education. Keywords: Social Environment, Self-Potential, Career Opportunities, Interest in Continuing Higher Education.